The Improvement of Problem-Solving Skills and Physics Concept Mastery on Temperature and Heat Topic - Batlolona, J. R.; Baskar, C.; Kurnaz, M. A.; Leasa, M. (Jurnal Pendidikan IPA Indonesia, 2018)
This work aimed at knowing the improvement of problem-solving and physics concept mastery by using the learning model of Hints and Peer Interaction Learning (HPIL) model. This research used embedded experimental model design, that one class could be used as a sample even though the sample size was less than 30 students. The number of the research sample was 22 students of one of the Senior High Schools in Malang. The instruments used were 25 numbers consisting of five numbers of the essay (problem-solving skill) and 20 numbers of multiple choices items (concept mastery). The data were analyzed by using paired sample t-test. The research results showed that there was an improvement in problem-solving skill from 40.68% to 74.77% and concept mastery from 0.48% to 0.72%. The result of the t-test indicated that the value of Sigcounting<Sigtable (0.00< 0.05); therefore, the problem-solving skills and concept mastery before and after the application of the HPIL was significantly different. The problem-solving skills required concept mastery or comprehensive knowledge from factual until metacognitive levels. Thus, teachers need to design suitable learning models to develop this basic knowledge as a foundation for developing problem-solving skills, one of them with HPIL.